The Correlation of Muhkam Verses with Nasikh and Mansukh in Islamic Legal Determination - Syukrinur, Syukrinur (Lembaga Aneuk Muda Peduli Umat, Bekerjasama dengan Pusat Jurnal Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
This study examines the correlation between muhkam verses and nasikh wal mansukh in determining Islamic legal rulings. Muhkam verses, characterized by their clear and explicit meanings, and nasikh wal mansukh, referring to the abrogation of certain laws within the Qur'an, are foundational concepts in 'ulum al-Qur'an. The research utilizes a qualitative methodology, involving detailed textual analysis of primary Qur'anic verses and secondary scholarly interpretations. The findings reveal that while muhkam verses provide explicit legal instructions, the principles of nasikh wal mansukh allow for the adaptation of these laws in response to changing social and historical contexts. This dynamic interplay ensures that Islamic legal rulings remain relevant and effective across different eras and circumstances. The study highlights the necessity of understanding the conditions and implications of abrogation in Islamic law and underscores the importance of contextual and scholarly engagement in the interpretation and application of Qur'anic teachings. This comprehensive analysis contributes to the broader discourse on the flexibility and timeless applicability of Islamic law, demonstrating its capacity to address contemporary legal challenges without contradicting core religious principles.